Analysis of Risk Management Strategies for Enhancing Business Sustainability in the Micro, Small, and Medium Enterprise (MSME) Sector - Syamsuriyanti (Maroon Journal De Management, 2024)
This study examines the impact of financial constraints, employee resistance, and external challenges on the implementation of effective risk management strategies in micro, small, and medium enterprises (MSMEs). Despite the growing recognition of the need for proactive risk management, MSMEs face significant barriers to adopting comprehensive frameworks due to limited financial resources, reluctance to embrace change, and the volatility of external market and regulatory environments. Financially constrained businesses often prioritize short-term survival over long-term risk mitigation, while employees resist the adoption of new technologies and risk management systems, slowing down potential improvements. Moreover, MSMEs are frequently confronted with external pressures, including economic instability and evolving regulatory requirements, which further hinder their ability to manage risks effectively. Through qualitative and quantitative analysis, this study provides valuable insights into the multifaceted challenges MSMEs face in adopting robust risk management practices and offers practical recommendations for overcoming these barriers. The findings underscore the importance of financial support, employee training, and strategic partnerships in enhancing MSMEs' resilience to external shocks and regulatory demands.